Field-induced hybridization of moiré excitons in MoSe$_2$/WS$_2$ heterobilayers - Polovnikov, Borislav; Scherzer, Johannes; Misra, Subhradeep; Huang, Xin; Mohl, Christian; Li, Zhijie; Göser, Jonas; Förste, Jonathan; Bilgin, Ismail; Watanabe, Kenji; Taniguchi, Takashi; Högele, Alexander; et al. (2023)
Phys. Rev. Lett. 132, 076902 (2024) We study experimentally and theoretically the hybridization among intralayer and interlayer moiré excitons in a MoSe$_2$/WS$_2$ heterostructure with antiparallel alignment. Using a dual-gate device and cryogenic white light reflectance and narrow-band laser modulation spectroscopy, we subject the moiré excitons in the MoSe$_2$/WS$_2$ heterostack to a perpendicular electric field, monitor the field-induced dispersion and hybridization of intralayer and interlayer moiré exciton states, and induce a cross-over from type I to type II band alignment. Moreover, we employ perpendicular magnetic fields to map out the dependence of the corresponding exciton Landé $g$-factors on the electric field. Finally, we develop an effective theoretical model combining resonant and non-resonant contributions to moiré potentials to explain the observed phenomenology, and highlight the relevance of interlayer coupling for structures with close energetic band alignment as in MoSe$_2$/WS$_2$.